Antibacterial Activity and Mechanism of the Gallnut Water Extract against Vibrio parahaemolyticus. Issue 4 (16th April 2022) - Yuan, Chunying; Zhan, Wenhao; Cui, Qingman
Abstract: Vibrio parahaemolyticus is an important pathogen causing pandemic diseases in marine animals and brings about severe economic losses in aquaculture worldwide. The emergence of multi‐drug‐resistant V. parahaemolyticus and the prohibition of antibiotics both require the development of new therapeutic agents with alternative action. In this study, the effect of gallnut Galla chinensis water extract (GWE) on V. parahaemolyticus growth and virulence was investigated to determine the potential for its use in disease prevention and treatment in aquaculture. The minimum inhibitory concentration and minimum bactericidal concentration of GWE against V. parahaemolyticus were identified as 0.49 and 0.98 mg/mL, respectively. Membrane damage in V. parahaemolyticus was further verified through the increase of conductivity and leakage of nucleic acids and proteins. Moreover, GWE caused membrane invaginations and damage in V. parahaemolyticus as observed via scanning electron microscopy. After treatment with GWE, the biofilm formation and the activities of respiratory chain dehydrogenase, lactate dehydrogenase, and succinate dehydrogenase of V. parahaemolyticus were all significantly inhibited. These findings suggest that GWE has the potential to be developed as a supplemental agent to mitigate the infections caused by V. parahaemolyticus in aquaculture.